2019
DOI: 10.1101/675835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal Cortex Regulates Chronic Stress-Induced Cardiovascular Susceptibility

Abstract: Key Points• Knockdown of glutamate release from infralimbic cortex increases heart rate and arterial pressure reactivity • Reduced infralimbic glutamate release increases cumulative arterial pressure during chronic variable stress • Decreased infralimbic glutamate output leads to vascular dysfunction after chronic stress• These functional changes associate with histological indicators of cardiac hypertrophy, as well as vascular hypertrophy and fibrosis. Running TitleCortical regulation of cardiovascular respon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In our study, a significant increase in the MAP occurred after 4 weeks of CUMS in normotensive WKY rats. Others have shown that chronic mild stress for 3 weeks does not significantly increase the MAP in normotensive rats (Grippo et al, 2002;Schaeuble et al, 2019). To date, brain regions involved in CUMS-induced chronic hypertension have not been specifically identified.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, a significant increase in the MAP occurred after 4 weeks of CUMS in normotensive WKY rats. Others have shown that chronic mild stress for 3 weeks does not significantly increase the MAP in normotensive rats (Grippo et al, 2002;Schaeuble et al, 2019). To date, brain regions involved in CUMS-induced chronic hypertension have not been specifically identified.…”
Section: Discussionmentioning
confidence: 98%
“…The rise in coronary tone in females is relevant to increased risk of mental stress‐related infarction (Vaccarino et al, 2014, 2018), which is thought to involve coronary microvascular abnormalities (Almuwaqqat et al, 2019). Chronic stress has recently been shown to impair endothelial‐dependent dilation in ex vivo aortic segments, a response mitigated by cortical glutamate signaling (Schaeuble et al, 2019). Such a pathway may similarly influence coronary microvascular control, and potentially impair vascular reactivity more widely, including within hepatic and cerebral circulations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, stressrelated disorders such as depression and post-traumatic stress disorder associate with altered structure and function of the vmPFC (Drevets et al, 1997;Drevets et al, 2008;Hamani et al, 2011;Liotti et al, 2000). In rodents, male vmPFC glutamate neurons promote socio-motivational behaviors and reduce physiological stress responses including hyperglycemia, tachycardia, and corticosterone release (Myers et al, 2017;Schaeuble et al, 2019;Wallace et al, 2021). Notably, vmPFC neurons do not directly project to neurosecretory cells or preganglionic sympathetic neurons, requiring intervening effector(s) to modulate physiological responses (Ulrich-Lai & Herman, 2009).…”
Section: Introductionmentioning
confidence: 99%